Check of a threshold of sensitivity and work without loading of static watt-hour meters - Петрище, М.О. (Proceedings of National Aviation University, 2004)
The analysis of requirements of activity of Ukraine interstate standard on static watt-hour meters for active energy of an alternating current (classes accurasy1 and 2) to check of a threshold of sensitivity and absence of a self-feed is lead. Lacks of requirements and technique recommendations on their elimination are specified. The technique of check of absence of a self-feed, which allows reducing considerably time for carrying out of this test, is developed.